The Interactionist Imagination : Studying Meaning, Situation and Micro-Social Order - Jacobsen, Michael Hviid (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book outlines the history and developments of interactionist social thought through a consideration of its key figures. Arranged chronologically, each chapter illustrates the impact that individual sociologists working within an interactionism framework have had on interactionism as perspective and on the discipline of sociology as such. It presents analyses of interactionist theorists from Georg Simmel through to Herbert Bulmer and Erving Goffman and onto the more recent contributions of Arlie R. Hochschild and Gary Alan Fine. Through an engagement with the latest scholarship this work shows that in a discipline often focused on macrosocial developments and large-scale structures, the interactionist perspective which privileges the study of human interaction has continued relevance. The broad scope of this book will make it an invaluable resource for scholars and students of sociology, social theory, cultural studies, media studies, social psychology, criminology and anthropology.